The Effect of 2-Thioxo Imidazolidin-4-Ones (2- Thiohydantion) on Anticancer Activity: An in Vitro Study - Mutashar Jiheel1 , Aseel Al –Rekaabi2 , Nasser Alqurashy1 , Mahdi Al – Deresawi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Purpose: Cancer is one of the most common factors of death in society today. Despitemuch research into cancer and its treatment, it is still one of the greatest health problems. The biggestobstacle to cancer treatment is that they are inherently resistant to chemotherapy or become drug resistantduring treatment. For this reason, researchers around the world have made great efforts to identify newnatural or synthetic compounds with anticancer properties. So the aim of this study is to find out the effectof 2-Thioxo imidazolidin-4-ones (2-Thiohydantion) on anticancer activity.Materials and Methods: Imidazoles are compounds that have antibacterial, antifungal and antitumorproperties in many studies. Through the results of this study, we discovered effectiveness of the newcompound of 2-Thioxo imidazolidin-4-ones (2 Thiohydantion) as an anticancer agent against a cell line thatis a cancer model system. To determine the IC50 of this compound, we treated the cancer cells by differentconcentrations (10, 20, 30, 40, 80 and 160 ?g / ml) and then the cells were evaluated by MTT assay after 24and 48 hour intervals.Results: After preparing the required compound, MTT assay showed that the IC50 of 2-Thioxo imidazolidin4-ones (2-Thiohydantion) compound on MCF7 cells, 135 and 40 ?g / ml, respectively, after 24 and 48 h,respectively. In addition, the toxicity of these compounds on normal cells was evaluated, which is verydifferent from their toxicity for cancer cells, and this is a very important feature. 2-Thioxo imidazolidin-4-ones (2-Thiohydantion) has the ability to stimulate cell death in cancer cells, and these results provide newinsights into the use of these compounds in cancer treatment.Conclusion: So 2-Thioxo imidazolidin-4-ones (2-Thiohydantion) at different concentrations significantlyreduced the growth of cancer cells compared to the control group (50% inhibition of cell growth). Futurestudies will need to investigate the mechanism of this cytotoxicity as well as the possible anticancereffectiveness of this compound in vitro and in vivo.